Awareness Questionnaire Versi Bahasa Indonesia untuk Pasien Chronic Kidney Disease (CKD) dengan Hemodialisa: Pengembangan Dan Validitas - Maria Putri Sari Utami; Brigitta Ayu Dwi Susanti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Chronic kidney disease (CKD) is a global health burden with high economic costs to the health system and is an independent risk factor for cardiovascular disease (CVD). All stages of CKD are associated with an increased risk of morbidity, premature mortality, and/or decreased quality of life. Therefore, there is a need for questionnaires for awareness-related measurements in CKD patients but to date, there is no validated awareness questionnaire for CKD patients. Aim: Develop an awareness questionnaire for the Indonesian version of CKD patients. Method: Descriptive research by conducting validity and reliability tests. Research is quantitative, where the inter-pretenseence of research results is based on static-tic processed results using computer applications. This research was conducted in the hemodialysis unit of Nitipuran Clinic, Yogyakarta. The data collection process in this study was carried out in December-April 2021. The study subjects were 52 hemodialysis patients. Results: The validity test of the awareness questionnaire contained 12 valid question items. The internal consistency value of consciousness indicates a cronbach'sα value of 0.865 this indicates that the questionnaire reliability test is classified as excellent reliability. This questionnaire can be used as an assessment instrument to find out the level of awareness of hemodialysis patients as preliminary data in determining the proper implementation. Conclusion: Awareness Questionnaire Version Indonesian can be used to determine the level of awareness of CKD patients with hemodialysis